Misleading free thyroxine (FT4): a case report - Hashim, Nurul Hidayah; Samsudin, Intan Nureslyna; Masiman, Ana Daliela; Chellappah Thambiah, Subashini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Interpretation of thyroid function test (TFT) is often straightforward but in certain scenarios, discordance between the clinical impression and the laboratory results exists. A 50-year-old woman with a ten years history of hypothyroidism on levothyroxine presented with a recent notable change in TFT [elevated free thyroxine (FT4) and thyroid-stimulating hormone (TSH)], in an otherwise clinically euthyroid and previously stable TFT, leading to levothyroxine being withheld. This case report highlights the possibility of assay interference as a cause of discordant TFT. It also draws the importance of close collaboration between clinicians and the laboratory to avoid unnecessary investigations and inappropriate management of such a case.